1995
DOI: 10.1111/j.1476-5381.1995.tb17198.x
|View full text |Cite
|
Sign up to set email alerts
|

Different pressor and bronchoconstrictor properties of human big‐endothelin‐1, 2 (1–38) and 3 in ketamine/xylazine‐anaesthetized guinea‐pigs

Abstract: Texas 75235-9050, U.S.A.1 In the present study, the precursors of endothelin-1, endothelin-2 and endothelin-3 were tested for their pressor and bronchoconstrictor properties in the anaesthetized guinea-pig. In addition, the effects of big-endothelin-l and endothelin-l were assessed under urethane or ketamine/xylazine anaesthesia. 2 When compared to ketamine/xylazine, urethane markedly depressed the pressor and bronchoconstrictor properties of endothelin-1 and big-endothelin-1. 3 Under ketamine/xylazine anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
0
3

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 25 publications
(22 reference statements)
1
13
0
3
Order By: Relevance
“…This finding correlates well with the fact that the 3 natural endothelin isopeptides possess the same affinity for the ET B receptor. 17 On the other hand, we have recently shown that the pulmonary circulations of different animal species 8,9 are less efficient for conversion of big ET-2 versus big ET-1. First, in the present study, big ET-2 was much less potent than big ET-1 to induce phosphoramidon-sensitive increases in MAP.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This finding correlates well with the fact that the 3 natural endothelin isopeptides possess the same affinity for the ET B receptor. 17 On the other hand, we have recently shown that the pulmonary circulations of different animal species 8,9 are less efficient for conversion of big ET-2 versus big ET-1. First, in the present study, big ET-2 was much less potent than big ET-1 to induce phosphoramidon-sensitive increases in MAP.…”
Section: Discussionmentioning
confidence: 99%
“…Given that phosphoramidon equally abolished the pressor responses to either big ET-1 or big ET-2, our results suggest a more effective conversion of big ET-1 than big ET-2 by ECE, which leads to spillover of ET-1 (but not ET-2) back into the vascular compartment to evoke activation of ET B receptor-dependent release of nitric oxide. If one considers that big ET-2 (1-38) is poorly converted in the pulmonary circulation of several species, 8,9 false ECE substrates derived from the structure of the ET-2 precursor may lead to moieties that interfere with the systemic production of ETs without affecting the delicate NO/ ET-1 balance in the lungs. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations